PERSPEKTIF ISLAM TERHADAP RADIKALISME, EKSTRIMISME DAN TERORISME DALAM KONTEKS AMAL MAK’RUF NAHI MUNGKAR - Hidayat, Khairul; Rasyid, Daud; Al Musawa, Nabiel; Hayatuddin, Hayatuddin; Evalinda, Evalinda; Farhana, Nurfitria; Nurhaidah, Siti Nuri; Hamid, Lallo (TAZKIRAH, 2025)
The focus of this study is on the issues of radicalism and terrorism. In today’s world, the problems of extremism, fundamentalism and radicalism are mainly known. Crime or violence is a phenomenon that we often hear and see in the mass media and it is also a reality in our surroundings and society. The most current happening and lively discussion in the media and public revolves around terrorism. Terrorism is consistently associated with fear, aggression, radicalism, and coercion, frequently resulting in adverse outcomes such as casualties. Extremism does not align with the principles of Islam, making it unsuitable to associate it with Islam, as radicalism is non-existent within Islam. In the Qur’an and Hadith, believers are commanded to respect and love one another as well as to be kind to others even if they are followers of other religions.Muslims are not the ones who initiate violence in the form of war or other forms of violence. Similarly, in the account of the Prophet Muhammad’s visit, including the battles of Badr and Uhud, it was not the Muslims who initiated the conflict with the non-believers, but rather the other way around.The study titled "Radicalism, Liberalism and Terrorism: Their Impact on Islam" analyzes the occurrences in the world both in general and in relation to issues of extremism, fundamentalism and religious radicalism. The descriptive method used by researchers is a method of studying the state of groups of people, conditions, systems of thought or phenomena at a particular point in time. To produce a systematic, factual and precise description of the facts, characteristics and relationships between the phenomena under study.